HORNBLENDE-GARNET-PLAGIOCLASE THERMOBAROMETRY: A NATURAL ASSEMBLAGE CALIBRATION OF THE THERMODYNAMICS OF HORNBLENDE - Dale J.; Holland T.; Powell R. (My University, 2000)
Calibrations are presented for an independent set of four equilibria between end-members of garnet, hornblende, plagioclase and quartz. Thermodynamic data from a large internally-consistent thermodynamic dataset are used to determine the ΔG° of the equilibria. Then, with the known mixing properties of garnet and plagioclase, the non-ideal mixing in amphibole is derived from a set of 74 natural garnet-amphibole-plagioclase-quartz assemblages crystallised in the range 4-13 kbar and 500-800 °C. The advantage of using known thermodynamic data to calculate ΔG° is that correlated variations of composition with temperature and pressure are not manifested in fictive derived entropies and volumes, but are accounted for with non-ideal mixing terms. The amphibole is modelled using a set of ten independent end-members whose mixing parameters are in good agreement with the small amount of data available in the literature. The equilibria used to calibrate the amphibole non-ideal mixing reproduce pressures and temperatures with average absolute deviations of 1.1 kbar and 35 °C using an average pressure-temperature approach, and 0.8 kbar with an average pressure approach. The mixing data provide not only a basis for thermobarometry involving additional phases, but also for calculation of phase diagrams in complex amphibole-bearing systems.